Preparation method of ultra-thin high-density fiberboard with ultra-low formaldehyde emission
By using melamine-modified urea formaldehyde resin and nanotitanium dioxide photocatalyst in the production of ultra-thin fiberboards, combined with specific process flow, the problem that ultra-thin fiberboards are difficult to take into account high strength when reducing formaldehyde emission, and low formaldehyde emission and High intensity.
Patent Information
- Application Number
- CN202411718646.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
While reducing the formaldehyde emission, existing ultra-thin fiberboards are difficult to take into account high strength, and the cost of aldehyde-free glue is high and the production process is complex.
The melamine-modified urea-formaldehyde resin is used as the adhesive, and the formaldehyde emission is reduced through specific shaving, hot grinding and hot pressing processes.
It has achieved a balance of ultra-low formaldehyde emission and high intensity, and has reduced the formaldehyde emission to reach F☆☆☆☆☆ Environmental protection level, and complies with the standards and requirements of the China Forestry Industry Association.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiberboard production, and in particular relates to a method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission. Background Art
[0002] Ultra-thin fiberboard refers to fiberboard with a thickness of less than 1.5 mm, especially high-density fiberboard with a thickness of less than 1.5 mm, where the high-density requirement specifically refers to a density of ≥ 0.8 g / cm 3 . On the one hand, ultra-thin fiberboard can be used as a finishing material to replace the existing high-tech wood and poplar decorative veneer to produce ultra-flat, skin-feeling, high-gloss and other high-end furniture, solving the problems of carbonization, unevenness, easy cracking and other problems after furniture surface decoration; on the other hand, it can be used as a balanced finishing for high-end solid wood composite flooring, with the characteristics of high strength, deformation resistance, and strong dimensional stability; in addition, functional ultra-thin fiberboard can also be used as green and environmentally friendly packaging materials for high-end gift boxes, which is greener and more environmentally friendly than ordinary paper materials. At present, the production process and equipment of ultra-thin fiberboard are relatively mature, and now have the ability to manufacture ultra-thin fiberboard with a minimum board thickness of 0.8mm, but the formaldehyde emission of ultra-thin fiberboard is difficult to control, and it is difficult to balance low formaldehyde emission and high strength. In order to reduce the formaldehyde emission of ultra-thin fiberboard in the prior art, a proposal for formaldehyde-free ultra-thin fiberboard has emerged, but the cost of formaldehyde-free glue is high, and the additional effects such as pipeline adhesion brought by the production process are large. Summary of the invention
[0003] In view of the above shortcomings, the present invention discloses a method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission. The prepared ultra-thin high-density fiberboard has the advantages of high strength and low formaldehyde emission.
[0004] The present invention is achieved by adopting the following technical solutions: A method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission, comprising the following steps: (1) The wood is peeled by a debarking machine and then chipped to obtain wood chips. The wood chips are washed with water and placed in a cooking tank for cooking. The cooking temperature is 160-170°C, the steam pressure is 8-9 bar, and the cooking time is 3-4 minutes. This can improve the fiber separation efficiency and fiber separation uniformity and reduce energy consumption. (2) feeding the wood chips treated in step (1) into a hot mill, and simultaneously adding molten paraffin into the hot mill, with the grinding disc gap controlled to be ≤0.3 mm, and obtaining fibers after being treated in the hot mill; (3) Apply adhesive to the fiber obtained in step (2), wherein the amount of adhesive applied is 230-260 kg / m 3The adhesive is obtained by uniformly mixing urea-formaldehyde resin, nano titanium dioxide and ammonium chloride curing agent, and the weight ratio of the urea-formaldehyde resin, nano titanium dioxide and ammonium chloride curing agent is 100: (5-15): (1.5-3.0); (4) Drying the fibers uniformly mixed with the adhesive to a moisture content of 5-7%, sorting and removing the glue clusters, fiber clusters and fiber bundles, and then paving and forming a slab; (5) taking the slab obtained in step (4) and performing a hot pressing process to obtain a plate, wherein the hot pressing process comprises the following working conditions: a hot pressing temperature of 140 to 220° C., a four-stage hot pressing temperature zone, a high pressure zone pressure of 150 to 280 bar, a heat transfer zone pressure of 5 to 15 bar, a thickness determination zone pressure of 50 to 80 bar, and a hot pressing factor of 6.5 to 10.5 s / mm; (6) After the hot pressing process, the board is cooled and then sanded to obtain an ultra-thin high-density fiberboard with ultra-low formaldehyde emission.
[0005] Furthermore, in step (1), the wood chips are washed with water, preheated at 80-90°C, and then placed in a cooking tank for cooking. Cooking can improve the fiber separation efficiency and fiber separation uniformity, reduce energy consumption, and preheating can homogenize the moisture content of the wood chips, thereby improving the cooking effect of the wood chips.
[0006] Furthermore, in step (2), the amount of molten paraffin applied is 10.0 to 13.0 kg / m 3 .
[0007] Furthermore, among the fibers obtained through the treatment in step (2), fibers larger than 200 meshes account for 3-8% of the total fiber weight, fibers 150-200 meshes account for 70-80% of the total fiber weight, fibers 100-150 meshes account for 7-20% of the total fiber weight, and fibers smaller than 100 meshes account for 0-5% of the total fiber weight.
[0008] Furthermore, in step (3), the urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, melamine, urea and auxiliary agents in proportion for use; the weight of the melamine accounts for 15-20% of the total weight of the urea-formaldehyde resin, and the molar ratio of the formaldehyde to the sum of urea and melamine is 0.80-0.90; the weight of the auxiliary agent accounts for 1-5% of the total weight of the urea-formaldehyde resin, and the auxiliary agent includes the following components in parts by weight: 45-55 parts of sodium bentonite, 25-35 parts of triethylenediamine, 8-12 parts of anhydrous sodium sulfate, and 5-15 parts of polyvinyl alcohol; S2, taking formaldehyde in a reaction kettle, adding caustic soda solution to adjust the pH value to 6.5-7.5, then adding melamine in an amount of 50-55% of the total amount of melamine, then adding an auxiliary agent, stirring and heating to 55-60° C., sampling to detect the pH value, when the pH value is 6.5-7.5, adding urea and controlling the molar ratio of formaldehyde to urea to 6.0-6.5 to obtain a mixture A; S3, heating the mixture A in step S2 to 85°C, then adding urea and controlling the molar ratio of formaldehyde to urea to be 2.0-2.5, and then treating at 80-90°C for 20 minutes to obtain a mixture B; S4, taking the mixture B obtained in step S3, adding formic acid solution to adjust the pH value to 5.5-6.0, sampling and testing the pH value and viscosity value (measured by viscosity cup) every 5-10 minutes, when the viscosity reaches 20-22 seconds, adding caustic soda solution to adjust the pH value to 7.0-7.5, then adding urea and the remaining melamine and controlling the molar ratio of formaldehyde to urea to 1.5-1.8, reacting at 75-80° C., testing the pH value and viscosity value (measured by viscosity cup) every 5-10 minutes, and obtaining a mixture C when the viscosity reaches 22-25 seconds; S5. Take the mixture C obtained in step S4, add caustic soda solution to adjust the pH value to 8.0-8.5, then add urea and control the molar ratio of formaldehyde to urea to 1.0-1.3, and then stir for 10-30 minutes to obtain a mixture D; take the mixture D, add urea and control the molar ratio of formaldehyde to urea to 0.8-0.9, stir for 10-20 minutes and then cool to 45°C, then add caustic soda solution to adjust the pH value to 8.0-8.5, and the viscosity value is 16-20s, the solid content is 55.0-58.0%, and then cool to below 40°C to obtain melamine-modified urea-formaldehyde resin.
[0009] The preparation method of the melamine-modified urea-formaldehyde resin of the present invention is different from the traditional synthesis process, but adopts an acid-base synthesis process and adds a composite reinforcing agent at the same time. Among them, formaldehyde is fed once, urea is fed five times, melamine is fed twice, and reinforcing agents (sodium bentonite, triethylenediamine and polyvinyl alcohol) are added once to synthesize and prepare ultra-low formaldehyde release melamine-modified urea-formaldehyde resin. Melamine is fed once under acidic conditions, which can react more fully and play a major role in improving the moisture-proof and reinforcing properties of the adhesive; the molar ratio of formaldehyde to urea in the adhesive is low, and the water resistance and bonding strength of the adhesive are poor. In addition to introducing melamine modification, reinforcing agents need to be added; it has been tested that sodium bentonite plays a major reinforcing role, triethylenediamine mainly plays a role in promoting cross-linking and reaction, and polyvinyl alcohol mainly plays a role in improving the water resistance of the adhesive.
[0010] Furthermore, in step S2, after adding the auxiliary agent, stirring is carried out for 15 minutes, and then heating is carried out to 55-60°C.
[0011] Furthermore, the concentration of the caustic soda solution is 25-35%, and the concentration of the formic acid solution is 15-20%.
[0012] Compared with the prior art, this technical solution has the following beneficial effects: 1. In order to reduce the formaldehyde emission of ultra-thin fiberboards in the prior art, proposals for formaldehyde-free ultra-thin fiberboards have emerged, but the cost of formaldehyde-free glue is high, and the additional effects such as pipe adhesion brought about by the production process are large. However, the use of urea-formaldehyde resin to produce fiberboards often faces the problem of not being able to balance the strength performance and formaldehyde emission performance of the fiberboard. The present invention provides a preparation process for ultra-thin high-density fiberboards with ultra-low formaldehyde emission, and uses a newly developed high-strength melamine-modified urea-formaldehyde resin adhesive with ultra-low formaldehyde emission to reduce formaldehyde emission to an environmental protection grade of F☆☆☆☆. At the same time, by reasonably setting the chipping, hot grinding, and hot pressing processes, not only can the goal of thinner and higher-density fiberboards be achieved, but also the mechanical performance requirements can be met, especially in line with the China Forest Products Industry Association T / CNFPIA3007-2019 "Ultra-Thin High-Density Fiberboard" standard requirements.
[0013] 2. In the process of preparing and applying glue, the melamine-modified urea-formaldehyde resin and the nano-scale titanium dioxide active material (photocatalyst) are evenly mixed before being applied; during the storage and processing of the board, the titanium dioxide photocatalyst active material generates free hydroxyl radicals and active oxygen with extremely strong oxidizing ability under the action of light, and these free radicals with extremely strong oxidizing ability can be decomposed and can effectively degrade free formaldehyde in the board. DETAILED DESCRIPTION
[0014] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0015] Embodiment 1: A method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission, comprising the following steps: (1) The wood is peeled by a debarking machine and then chipped to obtain wood chips. The wood chips are washed with water, preheated at 85°C, and then placed in a cooking tank for cooking. The cooking temperature is 165°C, the steam pressure is 8.5 bar, and the cooking time is 3.5 min. (2) The wood chips treated in step (1) are fed into a heat refiner, and melted paraffin is added to the heat refiner at a rate of 11.0 kg / m 3 , the grinding disc gap is controlled at ≤0.3mm, and the fiber is obtained after being treated by a hot mill; Among the fibers obtained after treatment, fibers larger than 200 mesh account for 7% of the total fiber weight, fibers between 150 and 200 mesh account for 75% of the total fiber weight, fibers between 100 and 150 mesh account for 15% of the total fiber weight, and fibers smaller than 100 mesh account for 3% of the total fiber weight; (3) Apply adhesive to the fiber obtained in step (2), wherein the amount of adhesive applied is 240 kg / m 3 The adhesive is obtained by uniformly mixing urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent, and the weight ratio of the urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent is 100:10:2.5; (4) Drying the fibers uniformly mixed with the adhesive to a moisture content of 6%, sorting and removing the glue clusters, fiber clusters and fiber bundles, and then paving and forming a slab; (5) taking the slab obtained in step (4) and performing a hot pressing process to obtain a plate, wherein the hot pressing process includes the following working conditions: a hot pressing temperature of 140 to 220° C., a four-stage hot pressing temperature zone, a high pressure zone pressure of 150 to 280 bar, a heat transfer zone pressure of 5 to 15 bar, a thickness determination zone pressure of 50 to 80 bar, and a hot pressing factor of 6.5 to 10.5 s / mm; (6) Cooling the board after the hot pressing process and then sanding it to obtain an ultra-thin high-density fiberboard with ultra-low formaldehyde emission; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, melamine, urea and auxiliary agents in proportion for use; the weight of the melamine accounts for 16% of the total weight of the urea-formaldehyde resin, and the molar ratio of the formaldehyde to the sum of urea and melamine is 0.85; the weight of the auxiliary agent accounts for 3% of the total weight of the urea-formaldehyde resin, and the auxiliary agent includes the following components in parts by weight: 50 parts of sodium bentonite, 30 parts of triethylenediamine, 10 parts of anhydrous sodium sulfate, and 10 parts of polyvinyl alcohol; S2. Take formaldehyde in a reaction kettle, add caustic soda solution to adjust the pH value to 7.0, then add melamine in an amount of 52% of the total amount of melamine, then add an auxiliary agent and stir for 15 minutes, then heat to 56°C, take a sample to detect the pH value, the pH value should be between 6.5 and 7.5, add urea and control the molar ratio of formaldehyde to urea to be 6.2 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, heating the mixture A in step S2 to 85° C., then adding urea and controlling the molar ratio of formaldehyde to urea to be 2.2, and then keeping the mixture at 85° C. for 20 min to obtain a mixture B; S4, taking the mixture B obtained in step S3, adding formic acid solution to adjust the pH value to 5.8, sampling and testing the pH value and viscosity value (measured by viscosity cup) every 5-10 minutes, when the viscosity reaches 21 seconds, adding caustic soda solution to adjust the pH value to 7.2, then adding urea and the remaining melamine and controlling the molar ratio of formaldehyde to urea to be 1.6, reacting at 78-80° C., testing the pH value and viscosity value (measured by viscosity cup) every 5-10 minutes, and obtaining mixture C when the viscosity reaches 23 seconds; the concentration of the formic acid solution is 16%; S5. Take the mixture C obtained in step S4, add caustic soda solution to adjust the pH value to 8.2, then add urea and control the molar ratio of formaldehyde to urea to 1.1, and then stir for 20 minutes to obtain a mixture D; take the mixture D, add urea and control the molar ratio of formaldehyde to urea to 0.85, stir for 15 minutes and then cool to 45°C, then add caustic soda solution to adjust the pH value to 8.2, and then cool to below 40°C to obtain melamine-modified urea-formaldehyde resin, the detected viscosity value is 18s, and the solid content is 56.0%.
[0016] Embodiment 2: A method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission, comprising the following steps: (1) The wood is peeled by a debarking machine and then chipped to obtain wood chips. The wood chips are washed with water, preheated at 80°C, and then placed in a cooking tank for cooking. The cooking temperature is 160°C, the steam pressure is 9 bar, and the cooking time is 4 minutes; (2) The wood chips treated in step (1) are fed into a heat refiner, and melted paraffin is added to the heat refiner at a rate of 10.0 kg / m 3 , the grinding disc gap is controlled at ≤0.3mm, and the fiber is obtained after being treated by a hot mill; Among the fibers obtained after treatment, fibers larger than 200 mesh account for 3% of the total fiber weight, fibers between 150 and 200 mesh account for 80% of the total fiber weight, and fibers between 100 and 150 mesh account for 17% of the total fiber weight; (3) Apply adhesive to the fiber obtained in step (2), wherein the amount of adhesive applied is 230 kg / m 3 The adhesive is obtained by uniformly mixing urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent, and the weight ratio of the urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent is 100:10:2.0; (4) Drying the fibers uniformly mixed with the adhesive to a moisture content of 7%, sorting and removing the glue clusters, fiber clusters and fiber bundles, and then paving and forming a slab; (5) taking the slab obtained in step (4) and performing a hot pressing process to obtain a plate, wherein the hot pressing process comprises the following working conditions: a hot pressing temperature of 140 to 220° C., a four-stage hot pressing temperature zone, a high pressure zone pressure of 150 to 280 bar, a heat transfer zone pressure of 5 to 15 bar, a thickness determination zone pressure of 50 to 80 bar, and a hot pressing factor of 6.5 to 10.5 s / mm; (6) Cooling the board after the hot pressing process and then sanding it to obtain an ultra-thin high-density fiberboard with ultra-low formaldehyde emission; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, melamine, urea and auxiliary agents in proportion for later use; the weight of the melamine accounts for 15% of the total weight of the urea-formaldehyde resin, and the molar ratio of the formaldehyde to the sum of urea and melamine is 0.80; the weight of the auxiliary agent accounts for 1% of the total weight of the urea-formaldehyde resin, and the auxiliary agent includes the following components in parts by weight: 45 parts of sodium bentonite, 25 parts of triethylenediamine, 8 parts of anhydrous sodium sulfate, and 5 parts of polyvinyl alcohol; S2. Take formaldehyde in a reaction kettle, add caustic soda solution to adjust the pH value to 6.5, then add melamine in an amount of 50% of the total amount of melamine, then add an auxiliary agent and stir for 15 minutes, then heat to 55°C, take a sample to detect the pH value, the pH value should be between 6.5 and 7.5, add urea and control the molar ratio of formaldehyde to urea to be 6.0 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, heating the mixture A in step S2 to 85° C., then adding urea and controlling the molar ratio of formaldehyde to urea to be 2.0, and then keeping the mixture at 80° C. for 20 min to obtain a mixture B; S4, taking the mixture B obtained in step S3, adding formic acid solution to adjust the pH value to 5.5, sampling and testing the pH value and viscosity value (measured by viscosity cup) every 5-10 minutes, when the viscosity reaches 20 seconds, adding caustic soda solution to adjust the pH value to 7.0, then adding urea and the remaining melamine and controlling the molar ratio of formaldehyde to urea to be 1.5, reacting at 75-78° C., testing the pH value and viscosity value (measured by viscosity cup) every 5-10 minutes, and obtaining mixture C when the viscosity reaches 22 seconds; the concentration of the formic acid solution is 15%; S5. Take the mixture C obtained in step S4, add caustic soda solution to adjust the pH value to 8.0, then add urea and control the molar ratio of formaldehyde to urea to 1.0, and then stir for 10 minutes to obtain a mixture D; take the mixture D, add urea and control the molar ratio of formaldehyde to urea to 0.8, stir for 10 minutes and then cool to 45°C, then add caustic soda solution to adjust the pH value to 8.0, and then cool to below 40°C to obtain melamine-modified urea-formaldehyde resin, the detected viscosity value is 16s, and the solid content is 55.0%.
[0017] Embodiment 3: A method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission, comprising the following steps: (1) The wood is peeled by a debarking machine and then chipped to obtain wood chips. The wood chips are washed with water, preheated at 88°C, and then placed in a cooking tank for cooking. The cooking temperature is 168°C, the steam pressure is 8.5 bar, and the cooking time is 3.5 min. (2) The wood chips treated in step (1) are fed into a heat refiner and melted paraffin is added into the heat refiner at the same time. The amount of melted paraffin applied is 12.0 kg / m 3 , the grinding disc gap is controlled at ≤0.3mm, and the fiber is obtained after being treated by a hot mill; Among the fibers obtained after treatment, fibers larger than 200 mesh account for 8% of the total fiber weight, fibers between 150 and 200 mesh account for 70% of the total fiber weight, fibers between 100 and 150 mesh account for 20% of the total fiber weight, and fibers smaller than 100 mesh account for 2% of the total fiber weight; (3) Apply adhesive to the fiber obtained in step (2), wherein the amount of adhesive applied is 250 kg / m 3 The adhesive is obtained by uniformly mixing urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent, and the weight ratio of the urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent is 100:15:3.0; (4) Drying the fibers uniformly mixed with the adhesive to a moisture content of 6%, sorting and removing the glue clusters, fiber clusters and fiber bundles, and then paving and forming a slab; (5) taking the slab obtained in step (4) and performing a hot pressing process to obtain a plate, wherein the hot pressing process comprises the following working conditions: a hot pressing temperature of 140 to 220° C., a four-stage hot pressing temperature zone, a high pressure zone pressure of 150 to 280 bar, a heat transfer zone pressure of 5 to 15 bar, a thickness determination zone pressure of 50 to 80 bar, and a hot pressing factor of 6.5 to 10.5 s / mm; (6) Cooling the board after the hot pressing process and then sanding it to obtain an ultra-thin high-density fiberboard with ultra-low formaldehyde emission; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, melamine, urea and auxiliary agents in proportion for use; the weight of the melamine accounts for 18% of the total weight of the urea-formaldehyde resin, and the molar ratio of the formaldehyde to the sum of urea and melamine is 0.88; the weight of the auxiliary agent accounts for 4% of the total weight of the urea-formaldehyde resin, and the auxiliary agent includes the following components in parts by weight: 50 parts of sodium bentonite, 30 parts of triethylenediamine, 10 parts of anhydrous sodium sulfate, and 10 parts of polyvinyl alcohol; S2. Take formaldehyde in a reaction kettle, add caustic soda solution to adjust the pH value to 7.0, then add melamine in an amount of 54% of the total amount of melamine, then add an auxiliary agent and stir for 15 minutes, then heat to 58°C, take a sample to detect the pH value, the pH value should be between 6.5 and 7.5, add urea and control the molar ratio of formaldehyde to urea to be 6.4 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, heating the mixture A in step S2 to 85° C., then adding urea and controlling the molar ratio of formaldehyde to urea to be 2.4, and then treating at 88° C. for 20 min to obtain a mixture B; S4, taking the mixture B obtained in step S3, adding formic acid solution to adjust the pH value to 5.8, sampling and testing the pH value and viscosity value (measured by viscosity cup) every 5 to 10 minutes, when the viscosity reaches 21 seconds, adding caustic soda solution to adjust the pH value to 7.2, then adding urea and the remaining melamine and controlling the molar ratio of formaldehyde to urea to be 1.6, reacting at 75 to 80° C., testing the pH value and viscosity value (measured by viscosity cup) every 5 to 10 minutes, and obtaining a mixture C when the viscosity reaches 24 seconds; the concentration of the formic acid solution is 18%; S5. Take the mixture C obtained in step S4, add caustic soda solution to adjust the pH value to 8.2, then add urea and control the molar ratio of formaldehyde to urea to 1.2, and then stir for 25 minutes to obtain a mixture D; take the mixture D, add urea and control the molar ratio of formaldehyde to urea to 0.85, stir for 15 minutes and then cool to 45°C, then add caustic soda solution to adjust the pH value to 8.2, and then cool to below 40°C to obtain melamine-modified urea-formaldehyde resin, the detected viscosity value is 18s, and the solid content is 56.0%.
[0018] Embodiment 4: A method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission, comprising the following steps: (1) The wood is peeled by a debarking machine and then chipped to obtain wood chips. The wood chips are washed with water, preheated at 90°C, and then placed in a cooking tank for cooking. The cooking temperature is 170°C, the steam pressure is 8 bar, and the cooking time is 3 minutes; (2) The wood chips treated in step (1) are fed into a heat refiner, and melted paraffin is added to the heat refiner at a rate of 13.0 kg / m 3 , the grinding disc gap is controlled at ≤0.3mm, and the fiber is obtained after being treated by a hot mill; Among the fibers obtained after treatment, fibers larger than 200 mesh account for 5% of the total fiber weight, fibers between 150 and 200 mesh account for 70% of the total fiber weight, fibers between 100 and 150 mesh account for 20% of the total fiber weight, and fibers smaller than 100 mesh account for 5% of the total fiber weight; (3) Apply adhesive to the fiber obtained in step (2), wherein the amount of adhesive applied is 260 kg / m 3 The adhesive is obtained by uniformly mixing urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent, and the weight ratio of the urea-formaldehyde resin, nano-titanium dioxide and ammonium chloride curing agent is 100:15:2.5; (4) Drying the fibers uniformly mixed with the adhesive to a moisture content of 5%, sorting and removing the glue clusters, fiber clusters and fiber bundles, and then paving and forming a slab; (5) taking the slab obtained in step (4) and performing a hot pressing process to obtain a plate, wherein the hot pressing process comprises the following working conditions: a hot pressing temperature of 140 to 220° C., a four-stage hot pressing temperature zone, a high pressure zone pressure of 150 to 280 bar, a heat transfer zone pressure of 5 to 15 bar, a thickness determination zone pressure of 50 to 80 bar, and a hot pressing factor of 6.5 to 10.5 s / mm; (6) Cooling the board after the hot pressing process and then sanding it to obtain an ultra-thin high-density fiberboard with ultra-low formaldehyde emission; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, melamine, urea and auxiliary agents in proportion for use; the weight of the melamine accounts for 20% of the total weight of the urea-formaldehyde resin, and the molar ratio of the formaldehyde to the sum of urea and melamine is 0.90; the weight of the auxiliary agent accounts for 5% of the total weight of the urea-formaldehyde resin, and the auxiliary agent includes the following components in parts by weight: 55 parts of sodium bentonite, 35 parts of triethylenediamine, 12 parts of anhydrous sodium sulfate, and 15 parts of polyvinyl alcohol; S2. Take formaldehyde in a reaction kettle, add caustic soda solution to adjust the pH value to 7.5, then add melamine in an amount of 55% of the total amount of melamine, then add an auxiliary agent and stir for 15 minutes, then heat to 60°C, take a sample to detect the pH value, the pH value should be between 6.5 and 7.5, and add urea at the same time and control the molar ratio of formaldehyde to urea to be 6.5 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, heating the mixture A in step S2 to 85° C., then adding urea and controlling the molar ratio of formaldehyde to urea to be 2.5, and then treating at 90° C. for 20 min to obtain a mixture B; S4, taking the mixture B obtained in step S3, adding formic acid solution to adjust the pH value to 6.0, sampling and testing the pH value and viscosity value (measured by viscosity cup) every 5 to 10 minutes, when the viscosity reaches 22 seconds, adding caustic soda solution to adjust the pH value to 7.5, then adding urea and the remaining melamine and controlling the molar ratio of formaldehyde to urea to be 1.8, reacting at 80°C, testing the pH value and viscosity value (measured by viscosity cup) every 5 to 10 minutes, and obtaining a mixture C when the viscosity reaches 25 seconds; the concentration of the formic acid solution is 20%; S5. Take the mixture C obtained in step S4, add caustic soda solution to adjust the pH value to 8.5, then add urea and control the molar ratio of formaldehyde to urea to 1.3, and then stir for 30 minutes to obtain a mixture D; take the mixture D, add urea and control the molar ratio of formaldehyde to urea to 0.9, stir for 20 minutes and then cool to 45°C, then add caustic soda solution to adjust the pH value to 8.5, and then cool to below 40°C to obtain melamine-modified urea-formaldehyde resin, the detected viscosity value is 20s, and the solid content is 58.0%.
[0019] Experimental Example: A fiberboard with a thickness of 1.2 mm was prepared according to the method described in Examples 1 to 4, and performance tests were performed. The specific results are shown in Table 1.
[0020] Table 1 Performance test results of 1.2mm fiberboard
[0021] It can be seen from the data in Table 1 that the ultra-thin fiberboard prepared by the present invention has good mechanical properties and low formaldehyde emission, which can meet the requirements of Japanese standard JIS 5905.
[0022] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission, characterized in that: The following steps are involved: (1) The wood is peeled by a debarking machine and then chipped to obtain wood chips, which are washed with water and placed in a cooking tank for steaming at a temperature of 160-170°C, a steam pressure of 8-9 bar, and a cooking time of 3-4 minutes; (2) feeding the wood chips treated in step (1) into a hot mill, and simultaneously adding molten paraffin into the hot mill, with the grinding disc gap controlled to be ≤0.3 mm, and obtaining fibers after being treated in the hot mill; (3) Apply adhesive to the fiber obtained in step (2), wherein the amount of adhesive applied is 230-260 kg / m 3 The adhesive is obtained by uniformly mixing urea-formaldehyde resin, nano titanium dioxide and ammonium chloride curing agent, and the weight ratio of the urea-formaldehyde resin, nano titanium dioxide and ammonium chloride curing agent is 100: (5-15): (1.5-3.0); (4) Drying the fibers uniformly mixed with the adhesive to a moisture content of 5-7%, sorting and removing the glue clusters, fiber clusters and fiber bundles, and then paving and forming a slab; (5) taking the slab obtained in step (4) and performing a hot pressing process to obtain a plate, wherein the hot pressing process comprises the following working conditions: a hot pressing temperature of 140 to 220° C., a four-stage hot pressing temperature zone, a high pressure zone pressure of 150 to 280 bar, a heat transfer zone pressure of 5 to 15 bar, a thickness determination zone pressure of 50 to 80 bar, and a hot pressing factor of 6.5 to 10.5 s / mm; (6) After the hot pressing process, the board is cooled and then sanded to obtain an ultra-thin high-density fiberboard with ultra-low formaldehyde emission.
2. The method for preparing the ultra-thin high-density fiberboard with ultra-low formaldehyde emission according to claim 1, characterized in that: In step (1), the wood chips are washed with water, preheated at 80-90° C., and then placed in a cooking tank for cooking. Steaming can improve the fiber separation efficiency and fiber separation uniformity, reduce energy consumption, and preheating can homogenize the moisture content of wood chips and improve the cooking effect of wood chips.
3. The method for preparing the ultra-thin high-density fiberboard with ultra-low formaldehyde emission according to claim 1, characterized in that: In step (2), the amount of molten paraffin applied is 10.0 to 13.0 kg / m 3 .
4. The method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission according to claim 1, characterized in that: Among the fibers obtained by the treatment in step (2), fibers larger than 200 meshes account for 3-8% of the total fiber weight, fibers 150-200 meshes account for 70-80% of the total fiber weight, fibers 100-150 meshes account for 7-20% of the total fiber weight, and fibers smaller than 100 meshes account for 0-5% of the total fiber weight.
5. The method for preparing an ultra-thin high-density fiberboard with ultra-low formaldehyde emission according to claim 1, characterized in that: In step (3), the urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, melamine, urea and auxiliary agents in proportion for use; the weight of the melamine accounts for 15-20% of the total weight of the urea-formaldehyde resin, and the molar ratio of the formaldehyde to the sum of urea and melamine is 0.80-0.90; the weight of the auxiliary agent accounts for 1-5% of the total weight of the urea-formaldehyde resin, and the auxiliary agent includes the following components in parts by weight: 45-55 parts of sodium bentonite, 25-35 parts of triethylenediamine, 8-12 parts of anhydrous sodium sulfate, and 5-15 parts of polyvinyl alcohol; S2, taking formaldehyde in a reaction kettle, adding caustic soda solution to adjust the pH value to 6.5-7.5, then adding melamine in an amount of 50-55% of the total amount of melamine, then adding an auxiliary agent, stirring and heating to 55-60° C., sampling to detect the pH value, when the pH value is 6.5-7.5, adding urea and controlling the molar ratio of formaldehyde to urea to 6.0-6.5 to obtain a mixture A; S3, heating the mixture A in step S2 to 85°C, then adding urea and controlling the molar ratio of formaldehyde to urea to be 2.0-2.5, and then treating at 80-90°C for 20 minutes to obtain a mixture B; S4, taking the mixture B obtained in step S3, adding formic acid solution to adjust the pH value to 5.5-6.0, sampling and testing the pH value and viscosity value every 5-10 minutes, when the viscosity reaches 20-22 seconds, adding caustic soda solution to adjust the pH value to 7.0-7.5, then adding urea and the remaining melamine and controlling the molar ratio of formaldehyde to urea to 1.5-1.8, reacting at 75-80° C., testing the pH value and viscosity value every 5-10 minutes, and obtaining a mixture C when the viscosity reaches 22-25 seconds; S5. Take the mixture C obtained in step S4, add caustic soda solution to adjust the pH value to 8.0-8.5, then add urea and control the molar ratio of formaldehyde to urea to 1.0-1.3, and then stir for 10-30 minutes to obtain a mixture D; take the mixture D, add urea and control the molar ratio of formaldehyde to urea to 0.8-0.9, stir for 10-20 minutes and then cool to 45°C, then add caustic soda solution to adjust the pH value to 8.0-8.5, and the viscosity value is 16-20s, the solid content is 55.0-58.0%, and then cool to below 40°C to obtain melamine-modified urea-formaldehyde resin.
6. The method for preparing the ultra-thin high-density fiberboard with ultra-low formaldehyde emission according to claim 5, characterized in that: In step S2, the auxiliary agent is added and stirred for 15 minutes, and then heated to 55-60°C.
7. The method for preparing the ultra-thin high-density fiberboard with ultra-low formaldehyde emission according to claim 5, characterized in that: The concentration of the caustic soda solution is 25-35%, and the concentration of the formic acid solution is 15-20%.
Citation Information
Patent Citations
Manufacturing process for ultra light fiber board
CN102806591A
Nano titanium dioxide doped high-weather-resistance modified urea-formaldehyde resin adhesive for boards and preparation method thereof
CN105349076A
Melamine-urea cocondensed resin as well as preparation method and adhesive thereof
CN108276540A
Preparation method of fiberboard with ultra-thin and ultralow formaldehyde emission
CN109016059A
Preparation method of water-resistant melamine modified urea-formaldehyde resin with ultralow free formaldehyde content and application of water-resistant melamine modified urea-formaldehyde resin to commercial floor base material
CN114262418A
Cited By
Mildew-proof antibacterial ultrathin density board and preparation method thereof
CN120134415A
Method for preparing reinforced composite wood floor by adopting low-formaldehyde adhesive
CN120645289A
Vegetable protein composite modified urea-formaldehyde resin adhesive for ENF-grade artificial board and preparation method of vegetable protein composite modified urea-formaldehyde resin adhesive
CN120865821A
Preparation method of floor base material with deodorization and antibacterial functions
CN121083753A